2009
DOI: 10.1038/sc.2009.142
|View full text |Cite
|
Sign up to set email alerts
|

Care needs of persons with long-term spinal cord injury living at home in the Netherlands

Abstract: Study design: Cross-sectional survey. Objectives: To describe the care received, care needs and preventability of secondary conditions according to persons with long-term spinal cord injury (SCI) living at home. Setting: The Netherlands. Methods: A questionnaire was sent to all members of the Dutch SCI Patient Organisation. From a list of 26 SCI secondary conditions, participants chose the five conditions they perceived as most important. For each of these conditions, they described the type of care they recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 19 publications
5
51
1
1
Order By: Relevance
“…Caregivers also perform a range of duties and roles including support for ADLs, nursing care, prevention of secondary health conditions, housekeeping, emotional care and practical care (errands). 9,16,17,22 The range of duties and roles identified in these studies may help explain the range in amount of informal care. Although some studies may have had clear operational definitions of what constituted care, these varied widely across studies.…”
Section: Description Of Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers also perform a range of duties and roles including support for ADLs, nursing care, prevention of secondary health conditions, housekeeping, emotional care and practical care (errands). 9,16,17,22 The range of duties and roles identified in these studies may help explain the range in amount of informal care. Although some studies may have had clear operational definitions of what constituted care, these varied widely across studies.…”
Section: Description Of Caregiversmentioning
confidence: 99%
“…Table 2 lists descriptive studies that were included. Of these studies, one reported the results of research with caregivers themselves, 9 nine reported research with individuals with SCI 8,[16][17][18][19][20][21][22][23] and one reported results of research with both caregivers and individuals with SCI. 24 The study that reported research with caregivers only was specific to informal caregiving.…”
Section: Level Of Evidencementioning
confidence: 99%
“…Questions regarding social participation and daily life were adopted from van Loo et al 1 and the original Dutch version was translated into English. Secondary health conditions determined from this study were placed into a categorical checklist.…”
Section: Questionnairementioning
confidence: 99%
“…Research indicates individuals with SCI experience 8-14 secondary conditions per year with more than one condition typically occurring concurrently. [1][2][3] Respiratory infections, urinary tract infections, spasticity, pain, blood pressure, and pressure sores are common secondary conditions among the SCI population. As the leading causes of re-hospitalization and additional financial burden among individuals with SCI, secondary health conditions can also be disruptive to participation within one's life.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of B1000 Dutch individuals with SCI noted that a high percentage believed that certain physical complications were 'totally' preventable; this included 27% regarding bladder-related complications, 24% regarding bowel-related complications and 53% regarding PUs. 43 Moreover, the most important preventive mechanisms identified in this SCI population were linked to the following: adherence to key self-management behaviors, ensuring that high quality of care was being accessed, and taking advantage of good information related to SCI complications.…”
Section: Influence Of Depression In Sci H Krueger Et Almentioning
confidence: 99%